Ancient sedimentary plant DNA dataset from Batagay (B17), Yakutia ... - Courtin, Jérémy (Dryad, 2022)
Here we provide a dataset on genetic plant diversity retrieved from permafrost sedimentary ancient DNA (sedaDNA) of the Batagay megaslump, Yakutia. Our dataset encompasses sedaDNA sequence data of 10 sediment samples. We used a PCR-based metabarcoding approach combined with Next-Generation Sequencing to assess the past, local vegetation compositional changes around the megaslump. As a plant specific metabarcode we applied the established chloroplastidal P6 loop trnL marker for plant diversity assessment. PCR products were sequenced on one Illumina sequencing HiSeq 2500 run. ... : We extracted sedimentary DNA from the permafrost samples using the DNeasy PowerMax Soil Kit. We used a PCR-based metabarcoding approach combined with Next-Generation Sequencing. As a plant specific metabarcode we applied the established chloroplastidal P6 loop trnL marker for plant diversity assessment and amplified plant DNA from sedimentary DNA extracts. Resulting PCR products were replicated 3 times for each sample, which were sequenced on one Illumina sequencing run. The underlying data set consists of raw R1.fastq and R2.fastq files of the sequencing run, two scripts that explain how to use the OBITools pipeline for data analyses and how to prepare taxonomic databases with EcoPCR and OBITools, the tagfile needed for demultiplexing the sequence raw data into samples, two database files for taxonomic assignment and one final data files. ...